Long Noncoding RNA KCNQ1OT1 Targets miRNA Let-7a-5p to Regulate Osteoarthritis Development and Progression - Basit, Muhammad Abdul; Jeelani, Muhammad Muzzammil; Butt, Maheen; Khan, Muhammad Waqas (Archives of Clinical and Biomedical Research, 2022)
Background: Osteoarthritis (OA) is a common disease of the joints among old populace until today. The treatment possibilities and roles of miRNA and long non-coding RNA (lncRNA) in therapy of OA has previously been explored. However, the functional roles of Long noncoding RNA KCNQ1OT1 and miRNA let-7a-5p on Osteoarthritis development and progression remains unclear. This study aimed at investigating the influence of KCNQ1OT1 on let-7a-5p in moderation of OA development and advancement. Materials and Methods: RT-qPCR examined expression of KCNQ1OT1and let-7a-5p in cultured human primary chondrocyte cell lines. Cell transfection overexpressed or knocked down the genes and CCK-8 assay measured cell viability in the proliferation biomarkers Ki87 and PCNA. While caspase-8 and caspase-3 activity determined rate of apoptosis. Furthermore, luciferase assay analyzed the luciferase activity and western blotting analysis determined the protein expression of KCNQ1OT1 and let-7a-5p in proliferation and apoptosis biomarkers. Results: The results demonstrated that KCNQ1OT1 is upregulated in OA-mimic cells and promotes the cell viability. KCNQ1OT1 knockdown suppresses cell viability of OA cells. Furthermore KCNQ1OT1 directly binds the 3'-UTR of let-7a-5p to negatively regulate let-7a-5p expression and OA progression. While upregulated let-7a-5p abolishes the proliferation effect of KCNQ1OT1 in OA cells. Conclusion: In summary, our study provides further insights into the underlying molecular mechanisms of KCNQ1OT1 and let-7a-5p suggesting a novel therapeutic approach to OA.